On the necessity of a state provision for the education of the deaf and dumb, the blind, and the imbecile - Pim, Jonathan (Statistical and Social Inquiry Society of Ireland, 1864)
Your attention has already been called to the "necessity of a state provision for the education of the Deaf and Dumb of Ireland." My object on the present occasion is to call your attention again to this subject, and to the parallel case of the Blind; and also to bring particularly under your notice the claims of another portion of our population, which is even more heavily afflicted.
Read, Wednesday, January 20th, 1864
Keywords: Disabled services; Disabled education; 314.15